1994
DOI: 10.2105/ajph.84.12.1960
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive efficacy and acceptability of the female condom.

Abstract: OBJECTIVES. The purpose of the study was to determine the contraceptive efficacy of the female condom and to provide data about the device to the US Food and Drug Administration. METHODS. The clinical trial was conducted at six US sites and three sites in Latin America. Eligible subjects were in mutually monogamous relationships and agreed to use the female condom as their only means of contraception for 6 months. RESULTS. A total of 328 subjects contributed to the analysis of contraceptive efficacy. Twenty-tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(57 citation statements)
references
References 3 publications
1
55
0
1
Order By: Relevance
“…A Medline key word search of "female condom" at press time resulted in a listing of 123 articles on various aspects of safety, acceptability, and efficacy. While the first two have been well established 38,39 and rigorous studies on the contraceptive efficacy of the female condom have been done, [40][41][42] data on the efficacy against STI are limited, 43,44 and more studies, especially those involving long-term follow up, are needed.…”
Section: Comparative Time Line Of the Tampon And Female Condom: Wherementioning
confidence: 99%
“…A Medline key word search of "female condom" at press time resulted in a listing of 123 articles on various aspects of safety, acceptability, and efficacy. While the first two have been well established 38,39 and rigorous studies on the contraceptive efficacy of the female condom have been done, [40][41][42] data on the efficacy against STI are limited, 43,44 and more studies, especially those involving long-term follow up, are needed.…”
Section: Comparative Time Line Of the Tampon And Female Condom: Wherementioning
confidence: 99%
“…Research has confirmed the contraceptive efficacy of the female condom. 7,8 One study suggested prophylactic efficacy against vaginal trichomoniasis. 9 A study among commercial sex workers in Thailand suggested that adding the female condom as an option for protection decreases unprotected sex and STD incidence.…”
mentioning
confidence: 99%
“…12,13 Although some of the studies with US women merely assessed acceptability with potential users, [14][15][16][17] most assessed acceptability after trial use. 7,[18][19][20][21][22] High rates of trial use and fairly positive reactions to the female condom have been reported. 7,18,19 Many acceptability studies have been criticized, however, as overestimating acceptability due to selection bias because the women had to agree to try the device as a criterion for study inclusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, of the 221 US women, 33.5% discontinued, whereas 55.1% of the 107 Latin American women discontinued. Overall the very limited evidence available indicates that the female condom, when used consistently and correctly, can be a highly effective method of contraception 14 .…”
Section: Ef® Cacy In Preventing Pregnancymentioning
confidence: 99%